The Effect of Pre-Feeding Oral Stimulation on The Sucking Ability of LBW Babies in The NICU Room - Wahyuni, Erni; Kalsum, Umi; Nur Imamah, Indah (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The inability to drink in LBW is caused by weak sucking muscle ability and unstable oral ability and swallowing and breathing on LBW babies influenced by maturity of the structure of the brain and cranial nerves. The LBW babies taken care does not suck directly on the mother's breast, this is because the mother and baby are taken care for separately. Objective: To analyze the effect of Pre-Feeding Oral Stimulation on the sucking ability of LBW Babies in the NICU Room at Harapan Insan Sendawar General Hospital. Method: This study used experimental research with one group pre-test and post-test. The population in this study were all LBW infants who were treated in the NICU room. Results and Discussion: The result of research was gained that the average of baby's sucking ability before oral stimulation was 2.67 where the lowest value of sucking ability is 0 and the highest value of sucking ability was 6. The average of baby's sucking ability after oral stimulation is 3.73 where the lowest value of sucking ability was 1 and the highest value of sucking ability was 7. The Statistical test results by conducting Wilcoxon T test were found that the P value was 0.01. So, the p-value (0.01) is smaller than the alpha value (0.05), it means that the null hypothesis is rejected. Conclusion: There is an effect of Pre-Feeding Oral Stimulation on the Sucking Ability of LBW Babies in the NICU Room at Harapan Insan Sendawar General Hospital in the year 2022.